Finite Element Analysis of Reinforced Concrete Beams Strengthened with CFRP In Flexural (Diyala Journal of Engineering Sciences, 2009)
Numerical analyses are performed using the ANSYS finite element program to simulate reinforced concrete beams strengthened by carbon fiber reinforced polymer applied at the bottom of these beams. Nonlinear material behavior, as it relates to steel reinforcing bars and plain concrete, and linear behavior for carbon fiber reinforced polymer is simulated using appropriate constitutive models. The results showed that the general behavior of the finite element models represented by the load-deflection curves at midspan show good agreement with the test data from the previous researches. Also The crack patterns at the failure loads from the finite element models correspond well with the observed failure modes of the experimental beams. The Finite element models represented by this research can be used to work parametric study for the strengthening of beams with CFRP.